2020
DOI: 10.1007/s11528-020-00534-z
|View full text |Cite
|
Sign up to set email alerts
|

The Balance of Roles: Graduate Student Perspectives during the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has impacted personal and professional lives. Graduate students juggle a variety of roles and had to quickly adjust. In this article, six graduate students share their reflections regarding the influence of the pandemic on respective stages in their doctoral program. They provide unique personal and professional perspectives that depict their abrupt shift to remote working and remote learning. The intention of this article is to garner an understanding of graduate students' challenges dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 2 publications
0
27
1
2
Order By: Relevance
“…Recent commentaries suggested that students with caretaking responsibilities (e.g. childcare) may be particularly effected during COVID-19 [25,26]. We did not find any differences in either sex or caretaking responsibilities between the two groups of students in Sweden.…”
Section: Students With Caretaking Responsibilitiescontrasting
confidence: 76%
“…Recent commentaries suggested that students with caretaking responsibilities (e.g. childcare) may be particularly effected during COVID-19 [25,26]. We did not find any differences in either sex or caretaking responsibilities between the two groups of students in Sweden.…”
Section: Students With Caretaking Responsibilitiescontrasting
confidence: 76%
“…Online learning has its strengths and weaknesses. Students' perceptions on on-line learning are quite positive; on-line learning makes learning not monotonous only in the classroom, there is efficiency in time and materials that are easily accessible (Agarwal & Kaushik, 2020;Bal, Arslan, Budhrani, Mao, Novak, & Muljana, 2020). Besides, impacts of positive perceptions are felt by students of on-line learning that integrates ICT (Information, Communication, and Technology) (Lubis, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Tartavulea et al, 2020), including detecting challenges for students such as lack of digital equipment or balancing responsibilities (e.g. Adnan & Anwar, 2020;Bal et al, 2020). Another line focuses on teachers-their coping mechanisms, managing burnout risk, and transformative experiences (among others Hargreaves & Fullan, 2020;Kim & Asbury, 2020;Moss et al, 2020).…”
mentioning
confidence: 99%